Advances in transition-metal-catalyzed C-H bond oxygenation of amides - Vijaykumar, Muniyappa; Punji, Benudhar (Synthesis-Stuttgart, 2021)
C-O bond formation represents a fundamental chemical transformation in organic synthesis to develop valuably oxygenated (hetero)arenes. Particularly, the direct and regioselective C-H bond oxygenation of privileged amides, using a transition metal catalyst and a mild oxygenating source, is a step-economy and attractive approach. During the last decade, considerable progress has been realized in the direct C-H oxygenation of primary, secondary, and tertiary amides. This Short Review compiles the advances in transition-metal-catalyzed oxygenation of C(sp(2))-H and C(sp(3))-H bonds on various amides with diverse oxygenation sources. The review is categorized into two different major sections: (i) C(sp(2))-H oxygenation and (ii) C(sp(3))-H oxygenation. Each section is discussed based on the directing group (monodentate and bidentate) attached to the amide derivatives.
Keywords: Amides; C-H activation; directing group; Oxygenation; Transition Metal